The Effect of Distribution Efficiency, Technology Capability, And Customer Satisfaction on Sales Performance at PT Mandiri Cahaya Plastindo - Fikram Wijaya; Mario Andriaskiton; August Halomoan Siregar (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the effects of distribution efficiency, technological capability, and customer satisfaction on sales performance at PT Mandiri Cahaya Plastindo. A quantitative approach with a causal research design was employed. Data were collected from respondents associated with the company and analyzed using multiple linear regression to examine both partial and simultaneous relationships among variables. The results indicate that distribution efficiency has a positive and significant effect on sales performance, suggesting that timely delivery and effective logistics management contribute to improved sales outcomes. Technological capability shows a positive but insignificant effect, implying that the existing technological resources have not been fully integrated into customer-oriented and strategic business processes. Customer satisfaction has the strongest and most significant effect on sales performance, indicating that product quality, service responsiveness, and customer relationships are key determinants of sales success. Simultaneously, distribution efficiency, technological capability, and customer satisfaction significantly affect sales performance, with a coefficient of determination of 69.1%, while the remaining 30.9% is explained by other factors outside the model. These findings highlight the importance of improving distribution systems, optimizing the utilization of technology, and maintaining customer satisfaction to achieve sustainable sales performance and strengthen competitive advantage